Mean Platelet Volume as a Marker of Sepsis in Newborn - Patidar, Shashikant; Baghel, Prabhat Singh; Bajaj, Naresh (Journal of Nepal Paediatric Society, 2022)
Introduction: Neonatal sepsis is the leading cause of death in developing country like India and we need early diagnosis and treatment to prevent mortality so we require better diagnostic marker for sepsis. Mean platelet volume (MPV) is a measure of average platelet volume which represents inflammatory burden of disease. In our study MPV rises in septic neonates significantly and can be helpful to diagnose sepsis early with other blood counts. Methods: This case-control study was done on 500 newborns, out of which 452 included in study are classified into two groups that is group A (n = 226): apparently healthy neonates, group B (n = 226): diagnosed with neonatal sepsis by septic screening positive. All patients in the study were go through adequate valuation of their history, clinical examination, complete blood count including MPV, C-reactive protein (CRP) and blood culture. Results: Septic neonates showed statistically higher values of MPV than the control group. The diagnostic cut-off value of MPV NS was 10.2 fl. Conclusions: MPV which is a platelet index obtained from complete blood count can be used an additional marker along with established septic screen to ensure early diagnosis in neonatal sepsis.